#TrainingInHome - Home-based training during COVID-19 (SARS-COV2) pandemic: physical exercise and behavior-based approach - de Oliveira Neto, L.; Elsangedy, H. M.; de Oliveira Tavares, V. D.; Vazquez La Scala Teixeira, C.; Behm, D. G.; Da Silva-Grigoletto, M. E. (Revista Brasileira de Fisiologia do Exercisio, 2020)
Coronavirus is part of a group of viruses responsible for seasonally causing acute respiratory syndromes that can be accompanied from mild symptoms to severe conditions with a significant mortality rate. In addition to hygiene care, social distance is one of the most efficient strategies to mitigate the spread of the virus and reduce impacts on the world. Therefore, government strategies have directed efforts to ensure the isolation at home of much of the world`s population. One of the strategies that has been considered an important tool to facilitate adherence to isolation is the encouragement of regular physical exercise, especially due to its ability to reduce feelings of anxiety and stress in the population. Thus, in parallel with the expansion of coronavirus in the world, the search for exercise at home has gained prominence on the internet, demonstrating the emerging need to think of strategies that can lead to an effective home practice in promoting adherence to a physically active lifestyle. On the other hand, some pertinent questions may arise, such as: how will the exercise prescription and follow-up of the population be carried out during this period? What guidelines should be followed for a safe and efficient prescription? What types of exercises should be prioritized? What are the criteria for this selection? Based on these questions, this study aimed to present a proposal, integrating the physiological and psychobiological aspects, of how physical exercise could be prescribed at home, considering the barriers faced by the population in the face of social isolation worldwide. In summary, here we suggest a prescription model that estimates the weekly performance of at least 150 minutes of aerobic exercises, as well as strength exercises for the main muscle groups. In addition, we guide the use of tools that allow the assessment of physical effort and personal satisfaction in training, with the aim of improving adherence and maintenance to a physical exercise program and thus contributing to health promotion during the COVID-19 pandemic.